Land Use Changes in Batang Suliti Watershed using ArcGIS - Putra, Robby Eldy Eka; Junaidi; Andriani (Universitas Negeri Padang, 2025)
The ArcGIS application can process satellite imagery data into a land use map and calculate the area of each land use type. This study analyzes land use changes in the Batang Suliti watershed from 2013 to 2022 using ArcGIS. The study employs supervised classification and cloud masking techniques to enhance accuracy. The results indicate that forest area decreased by 4.47% with an annual change rate of 0.50%, followed by a 2.55% reduction in rice fields, while residential areas increased by 1.21%. These changes are mainly driven by population growth and agricultural expansion. The findings highlight the need for sustainable land use management policies to mitigate environmental degradation in the watershed.